The effect of flywheel training on strength and physical capacities in sporting and healthy populations: An umbrella review - de Keijzer, K. L.; Gonzalez, J. R.; Beato, M. (PLOS ONE, 2022)
The aim of this umbrella review was to provide a detailed summary of how flywheel training enhances strength and physical capacities in healthy and athletic populations. The eleven reviews included were analyzed for methodological quality according to the Assessing the Methodological Quality of Systematic Review 2 (AMSTAR 2) and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Two were systematic reviews, six were systematic reviews with meta-analyses and three were narrative reviews. Although the included reviews support use of flywheel training with athletic and healthy populations, the umbrella review highlights disparity in methodological quality and over-reporting of studies (38 studies were included overall). Flywheel post-activation performance enhancement protocols can effectively enhance strength and physical capacities acutely with athletes and healthy populations. All relevant reviews support flywheel training as a valid alternative to traditional resistance training for enhancing muscular strength, power, and jump performance with untrained and trained populations alike. Similarly, reviews included report flywheel training enhances change of direction performance—although conclusions are based on a limited number of investigations. However, the reviews investigating the effect of flywheel training on sprint performance highlight some inconsistency in attained improvements with elite athletes (e.g., soccer players). To optimize training outcomes, it is recommended practitioners individualize (i.e., create inertia-power or inertia-velocity profiles) and periodize flywheel training using the latest guidelines. This umbrella review provides an analysis of the literature`s strengths and limitations, creating a clear scope for future investigations.